Economic analysis of milk production in peri-urban dairy farms of Odisha - Acharya, Kamlesh Kumar; Malhotra, Ravinder (Indian Journal of Dairy Science, 2020)
East and South-eastern coastal plain zone of Odisha was purposively selected for conducting study. After complete enumeration farms were categorized into small, medium and large categories on the basis of milch animals using cumulative square root frequency method. A total of 120 peri-urban dairy farms were selected from two towns namely Bhubaneswar town (Khorda district) and Cuttack town (Cuttack district). Budgeting technique was used to estimate costs and returns. Capital recovery cost method was used to evaluate fixed costs and variable costs were also evaluated for estimation. From the analysis it was concluded that crossbred cows were more profitable as compared to buffaloes. Milk productivity and returns from per litre milk of crossbred cow were more than buffalo. Concentrate feeding constitute major share in total feeding expenditure. Among different herd size categories of dairy farms large farms were getting more profit per litre of milk than medium and small farms. Cost elasticity was estimated using Cobb-Douglas production function shows a negative relationship between per unit cost and milk yield.